The Leading Ladies of Traditional Theatre: A Contemporary Performances of Female Traditional Storyteller - Wahyuningtyas, Bhernadetta Pravita; Sumbogo, Tri Adi; Zulqarnain, Wajid (Institut Komunikasi dan Bisnis LSPR, 2023)
This study captured that female traditional performer possess inherent qualities that make them ideal for public relations roles in provide not only local but also national branding globally. Their ability to captivate people, communicate effectively, and adapt to different situations gives them an edge over traditional PR representative today. The phenomenon is considered in relation to the changing function of traditional performances from popular entertainment purposes only to cultural preservation during rapid modernization process world widely. This study used qualitative methods with constructivist paradigm approach, interview, and observation in gathered the data. Female traditional performer or storyteller are the public relations representative for the traditional culture of Indonesia. For the driven cannot only be happened without intervened of the government through education system. This study focuses on traditional storytelling performances, and the observation of concerts and rehearsals of it especially in Central Java, Indonesia. Through this fieldwork, several communication issues became relevant. By integrating performers into PR campaigns through collaborative events, social media campaigns, or as brand ambassadors, organizations can harness their unique talents to achieve remarkable results. Embracing performers as PR representatives is a forward-thinking approach that embraces creativity and enhances communication arena visibility in today's increasingly competitive landscape.